Research on passive control of cloud cavitation based on a bionic fin-fin structure. Issue 3 (23rd September 2019) - Zhao, W.G.; Wang, Guipeng
Abstract : Purpose: The purpose of this paper is to use the NACA 0015 symmetric hydrofoil as the research subject and control cloud cavitation on hydrofoils. Design/methodology/approach: Based on observed distribution of caudal fin spines on fish, a bionic structure of fin-like spines is arranged on the hydrofoil suction surface, which maintains the cavitation in a quasi-steady state stage by eliminating the cyclic shedding process of cloud cavitation. Based on the modified shear stress transport k-ω turbulence model and the Zwart–Gerber–Belamri cavitation model, this paper compares and analyzes the NACA 0015 hydrofoil and the bionic NACA 0015 hydrofoil under condition of an angle of attack of 8° and a cavitation number of 0.8. Findings: The results show that the average drag of the hydrofoil is reduced but the lift is decreased, and the lift-drag ratio is increased after arranging the bionic structure. The bionic structure can effectively reduce the turbulent kinetic energy and make the flow more stable; it also can effectively control the hydrofoil surface side-entrant jet and the vortex shedding process of the near wall region. Originality/value: Based on the above conclusions, the bionic structure of fin-like spines can achieve a significant passive control in the hydrofoil cloud cavitation process.